Understanding Anti-Obesity Potential of Four Porphyrin Compounds by Investigating Pancreatic Lipase Inhibition - Jie Zhou; Xinrui Wang; Yangyuxin Liu; Xiaochen Li; Mingze Huang; Helong Bai; Jingang Mo (Molecules)
Obesity is a chronic epidemic caused by abnormal fat metabolism. As a key digestive enzyme, pancreatic lipase (PL) is an important target for regulating fat metabolism. The inhibitory potential of 5,10,15,20-Tetrakis (4-aminophenyl) porphyrin (TAPP), 5,10,15,20-Tetrakis (4-hydroxyphenyl) porphyrin (THPP), meso-Tetra (4-carboxyphenyl) porphine (TCPP), Cu (II) meso-Tetra (4-carboxyphenyl) porphine (Cu-TCPP) on PL was studied by enzymatic kinetics, multi-spectral, and molecular simulation technology. THPP, TCPP, TAPP, and Cu-TCPP all had good PL inhibitory activity (IC50 range: 97.49–248.70 μM) and were uncompetitive inhibitors. The order of inhibitory ability was: THPP > TCPP > TAPP > Cu-TCPP. The fluorescence quenching mechanism of THPP to PL was a mixed quenching dominated by static quenching, while TCPP, TAPP, and Cu-TCPP were static quenching. The binding of THPP, TCPP and TAPP to PL was mainly driven by hydrogen bonds and van der Waals forces, while Cu-TCPP was mainly driven by a hydrophobic interaction. Four porphyrin compounds changed the conformation of PL, affected the microenvironment of Tyr and Trp residues, and induced changes in the secondary structure of PL, thereby reducing the stability and catalytic activity of PL. Hydrogen bonds played an important role in the binding stability of THPP, TCPP, TAPP, and PL.